Modelling uncertainty in decision making : fuzzy performance measures and fuzzy target - Nunes, Eusébio P. (2011)
Decision making processes are based on performance measures that are compared with other performance measures values or with targets. Generally, the performance measure is only a number which do not consider the uncertainty associated with obtaining it such as measurement errors, precision and accuracy of measurement tools and subjective judgment. In this work, the uncertainty associated with performance measures is quantified through fuzzy numbers. The decision criterion is also represented by a fuzzy number. An indicator that considers both uncertainties in performance measure and decision criterion is developed. This indicator will help the decision maker once it quantifies the risk associated with the decision.